Social entrepreneurship and dynamic capabilities - Corner, P; Kearins, K (Academy of Management (AOM), 2013)
This paper investigates how dynamic capabilities form in the context of social entrepreneurship. A qualitative, inductive approach is used to examine four cases of ventures founded to solve social problems. Findings from within and cross case analysis revealed overlapping patterns that coalesced into two microprocesses whereby social entrepreneurs amassed, configured and reconfigured resources in an effort to solve particular social problems. These are cobbling across sectors and effectuating ecosystems. Implications of findings for dynamic capabilities and social entrepreneurship are discussed including the intriguing idea that entrepreneurs found more than just social purpose ventures, they create capability platforms upon which others can build.
Keywords: Dynamic capabilities; Microprocesses in entrepreneurship; Social entrepreneurship